The Effect of Sales Strategies in the Financial Performance of Insurance Companies - Maroofi, Fakhraddin; Ardalan, Arman Ghasm; Tabarzadi, Jamil (International Journal of Asian Social Science, 2016)
The goal of this study, is to investigate the sales strategies in the financial performance of insurance companies in the Kurdistan province. The data were collected by the questionnaires, and analyzed. The reliability of the questionnaires was analyzed using Cronbach's alpha coefficient, which were 864/0 and 873/0 for the questionnaire of sales strategy and sales performance respectively. All hypotheses were confirmed in the 05/0 reliability and the results showed that the sales strategy has a significant impact on the performance. The relationship between the insurance companies and sales strategies (direct and indirect sales) performance (customer satisfaction and return on total assets) was significant approved. The correlation coefficients were 0.906, 0.939, 0.942 and 0.894.